Spatial and temporal variation of primary production of Patagonian wet meadows - Buono, Gustavo Gabriel; Oesterheld, Martin; Nakamatsu, Viviana Beatriz; Paruelo, José María (Elsevier, 2019)
In extra-Andean Patagonia, wet meadows contrast with the prevailing arid steppes, and present a gradient of water availability from the periphery to the center. The objectives of this paper are to describe the spatial and temporal variation of aerial net primary production (ANPP) of Patagonian meadows, and to obtain a model for the relationship between the normalized difference vegetation index (NDVI) and ANPP. We determined ANPP in four regionally scattered meadows during 3–5 years and in three positions of the gradient of water availability. In one meadow, we correlated ANPP with NDVI during 2 years. Annual ANPP was 2–3 times larger in the center than in the periphery, and also varied 2–3 fold among the four meadows. The interannual variation of ANPP was high and similar across meadows and zones. ANPP was closely correlated with NDVI through a linear model. Within the growing season, the central zone had a more extended period of high NDVI into the summer than the peripheral and the intermediate zones. We conclude that (1) the local variation of ANPP across the gradient of water availability is strong and must be taken into account for management, and (2) the highly variable ANPP may be monitored by remote sensing.